Sunlight and Culture - Fredriksson, Per G. (2022)
The effects of the individualism vs. collectivism cultural dichotomy on economic outcomes have been widely recognized in the literature. We propose and test the hypothesis that individuals and populations located in areas exposed long-term to more ultraviolet radiation (UV-R; sunlight) exhibit a greater degree of collectivism. We provide individual level evidence using data from the World Values Survey, evidence from pre-industrial societies using data from the Standard Cross-Cultural Sample, and cross-country findings. We propose that the mechanism works via the eye disease cataract. Populations exposed to higher amounts of UV-R have higher incidence of cataract. A greater probability of eye disease raises the level of uncertainty avoidance and risk aversion, and increases the importance of close family or village bonds, facilitating the emergence of collectivism. This has provided an insurance mechanism against income shocks associated with poor eyesight and blindness. Moreover, humans tend to view disabilities such as blindness to indicate a positive probability of being associated with pathogen threats, resulting in less out-group interaction and greater collectivism. Empirical evidence supports this mechanism.